Early Post-Transplant Leptin Concentration Changes in Kidney Transplant Recipients - Diana Sukackiene; Agne Laucyte-Cibulskiene; Ignas Badaras; Laurynas Rimsevicius; Valdas Banys; Dalius Vitkus; Marius Miglinas (Medicina, 2021)
Background and Objectives: Kidney transplant recipients represent a unique population with metabolic abnormalities, altered nutritional and immune status, as well as an imbalanced regulation of adipocytokine metabolism. Leptin is a hormonally active protein mainly produced by fat tissue that modulates appetite, satiety, and influences growth, energy, and bone metabolism. There has been great interest in the role of this hormone in chronic kidney disease-related protein energy wasting; thus, a positive leptin correlation with body mass index and fat mass was confirmed. This study was designed to determine the association of pre and post-kidney transplant leptin concentration with nutritional status and body composition. Materials and Methods: We studied 65 kidney transplant recipients. Nutritional status was evaluated before kidney transplantation and 6 months later using three different malnutrition screening tools (Subjective Global Assessment Scale (SGA), Malnutrition Inflammation Score (MIS), and Geriatric Nutritional Risk Index (GNRI)), anthropometric measurements, and body composition (bioelectrical impedance analysis (BIA)). Demographic profile, serum leptin levels, and other biochemical nutritional markers were collected. Statistical analysis was performed with R software. Results: Median age of the studied patients was 45 years, 42% were females, and 12% had diabetes. Leptin change was associated with body weight (p < 0.001), waist circumference (p < 0.001), fat mass (p < 0.001) and body fat percentage (p < 0.001), decrease in parathyroid hormone (PTH) (p < 0.001) transferrin (p < 0.001), diabetes mellitus (p = 0.010), and residual renal function (p = 0.039), but not dependent on dialysis vintage, estimated glomerular filtration rate (eGFR), or delayed graft function at any time during the study. After adjustment for age and sex, body mass index (BMI) (p < 0.001), fat mass (p < 0.001), and body fat percentage (p < 0.001) were independent variables significantly associated with post-transplant leptin change. Lower leptin values were found both before and after kidney transplantation in the SGA B group. GNRI as a nutritional status tool was strongly positively related to changes in leptin within the 6-month follow-up period. Conclusions: Kidney transplant recipients experience change in leptin concentration mainly due to an increase in fat mass and loss of muscle mass. GNRI score as compared to SGA or MIS score identifies patients in whom leptin concentration is increasing alongside an accumulation of fat and decreasing muscle mass. Leptin concentration evaluation in combination with BIA, handgrip strength measurement, and GNRI assessment are tools of importance in defining nutrition status in the early post-kidney transplant period.